2021
DOI: 10.1186/s12967-020-02684-3
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of urinary tract symptoms and quality of life in benign prostate hyperplasia patients associated with consumption of a newly developed whole tomato-based food supplement: a phase II prospective, randomized double-blinded, placebo-controlled study

Abstract: Background Benign prostatic hyperplasia (BPH) is the most common urologic disease among elderly men. The diagnosis of BPH is usually driven by lower urinary tract symptoms (LUTS) that can significantly affect patients’ quality of life. This phase II prospective, randomized double-blinded, placebo-controlled study aimed to determine the efficacy and safety of a novel whole tomato-based food supplement on LUTS of patients diagnosed with BPH. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
1
11
0
1
Order By: Relevance
“…However, these positive effects were not statistically significant, and the size of changes is clinically notable. In agreement with our findings, Cormio et al reported that consumption of whole tomato food supplement (WTFS), which may contain both lycopene and FruHis, decreases the symptom score from 9.05 to 7.15 and improves QoL, about one score, in patients with BPH ( 43 ). In the mentioned study, these changes were not significant compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…However, these positive effects were not statistically significant, and the size of changes is clinically notable. In agreement with our findings, Cormio et al reported that consumption of whole tomato food supplement (WTFS), which may contain both lycopene and FruHis, decreases the symptom score from 9.05 to 7.15 and improves QoL, about one score, in patients with BPH ( 43 ). In the mentioned study, these changes were not significant compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…The treatment of BPH-related LUTSs has changed markedly over the past 20-30 years, with a shift toward pharmacotherapy and management in primary care [1][2][3]. Until now, patients whose LUTSs become incapacitating have typically been offered TURP and, more recently, laser prostatectomy [2,8].…”
Section: Discussionmentioning
confidence: 99%
“…Benign prostatic hyperplasia (BPH) is associated with lower urinary tract symptoms (LUTSs) and quality-of-life (QoL) alterations in aging men [1]. Transurethral resection of the prostate (TURP) remains the standard of care for most patients with failure of, or intolerance to, first-line pharmacotherapy and/or specific food supplements [1][2][3]. However, TURP can be associated with complications such as bleeding, infection, and retrograde ejaculation [2].…”
Section: Introductionmentioning
confidence: 99%
“…EP2851080A1) derived from the combination of spray-dried whole tomatoes and a small percentage olive mill wastewater (98:2 ratio). The supplement was shown to possess potent antioxidant and anti-inflammatory activity in animal model [ 36 ] and human disease [ 37 ]. On the basis of its varied nutraceutical composition, this supplement could be a valid functional food to be included in a green diet plan; in addition, the employment of tomato scraps and olive oil production wastes gives a nod to the environment, allowing the recovery of potential contamination sources.…”
Section: Resultsmentioning
confidence: 99%